2021
DOI: 10.1590/1516-3180.2020.0442.r1.18112020
|View full text |Cite
|
Sign up to set email alerts
|

Poor sanitation and transmission of COVID-19 in Brazil

Abstract: The aim of this study was to analyze the COVID-19 pandemic in the context of unjust and avoidable inequalities (called iniquities) in Brazil. A bibliographic search of texts relating to basic sanitation, socioeconomic development and transmission of COVID-19 itself was carried out. The focus was on discussion of the pandemic and on making connections with Brazil's structural problems and comparisons with other countries, especially those of low to medium developmental level (i.e. similar to Brazil). COVID-19 T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 37 publications
0
6
0
1
Order By: Relevance
“…30-32 Taking the Brazilian context into a wider perspective, low- and middle-income countries (as compared to high income countries) are likely to have higher negative impacts on cancer care services due to a significant shortage of resources and health care personnel. 11,33…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…30-32 Taking the Brazilian context into a wider perspective, low- and middle-income countries (as compared to high income countries) are likely to have higher negative impacts on cancer care services due to a significant shortage of resources and health care personnel. 11,33…”
Section: Discussionmentioning
confidence: 99%
“…[30][31][32] Taking the Brazilian context into a wider perspective, low-and middle-income countries (as compared to high income countries) are likely to have higher negative impacts on cancer care services due to a significant shortage of resources and health care personnel. 11,33 Moreover, there is long-standing evidence of the inequality in hospital capacity across the regions in Brazil in terms of health infrastructure. A recent analysis reported that the median number of hospital beds in Brazil is 19 per 10 000, but 5% of the north's micro-regions have only six beds per 10 000.…”
Section: Discussionmentioning
confidence: 99%
“…In some vulnerable settlements, printed manuals and posters were distributed in addition to online and community radio campaigns [81] . In vulnerable urban areas such as favelas, the Covid-19 burden is more noticieable [4] ; therefore, a prevention policy and its communication must be differentiated, taking into account the socioeconomic characteristics of these areas, such as the lack or limited access to sanitation, the cost of personal hygiene products and the prevalence of the informal employment [89] .…”
Section: Discussionmentioning
confidence: 99%
“…This study shows that hospitals, PHC, and health workers become clusters of transmission of the virus. The COVID-19 Response Acceleration Task Force on September 23 stated that the cluster of patients at the hospital was the highest in Jakarta, with 24,400 positive patients, which is about 63.46% of the total cases in the province 71 . Another study also revealed that there had been transmission by 14 health workers (HCWs) infected with the virus at the Wuhan Union Hospital, China 72 .…”
Section: Discussionmentioning
confidence: 99%